2022
DOI: 10.3389/fpsyg.2022.1051803
|View full text |Cite
|
Sign up to set email alerts
|

ICT literacy, resilience and online learning self-efficacy between Chinese rural and urban primary school students

Abstract: In the process of large-scale online education during the COVID-19 pandemic, students’ online learning has caused widespread public concerns. This study investigated the relationships between Chinese rural and urban primary school students’ information communications technology (ICT) literacy, student resilience, and online learning self-efficacy in a large-scale online education environment during the pandemic in China. We compared 5,037 primary school students in rural areas to 5,045 primary school students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Correlation analysis showed that perceived social support was significantly related to nursing students' resilience, and further regression analysis found that perceived social support positively predicted nursing students' resilience, which is consistent with previous studies. 25,40,42 This suggests that the verbal motivation or support that nursing students subjectively experience from their families, peers, and teachers, amongst others, can enhance their resilience, enable them to adjust their mindset, and actively seek solutions to resist the adverse effects of their environment when faced with increasingly difficult professional studies, a rigorous examination system. Therefore, to promote nursing students' resilience, it is important to focus on uniting the strengths of schools, families, and society to provide adequate resources to support students.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis showed that perceived social support was significantly related to nursing students' resilience, and further regression analysis found that perceived social support positively predicted nursing students' resilience, which is consistent with previous studies. 25,40,42 This suggests that the verbal motivation or support that nursing students subjectively experience from their families, peers, and teachers, amongst others, can enhance their resilience, enable them to adjust their mindset, and actively seek solutions to resist the adverse effects of their environment when faced with increasingly difficult professional studies, a rigorous examination system. Therefore, to promote nursing students' resilience, it is important to focus on uniting the strengths of schools, families, and society to provide adequate resources to support students.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the challenges, the remote-learning environment has also brought about new educational opportunities ( Hoss et al, 2022 ; Li et al, 2022 ). For example, Azorín (2020) argues that the crisis provides scarce opportunities to trial, improve, and rethink the role, content, and innovative delivery methods of education.…”
Section: Literature Reviewmentioning
confidence: 99%